Implementasi Pembelajaran Berdiferensiasi dengan Model Discovery Learning pada Pelajaran Bahasa Indoneia Kelas XII di SMAN CMBBS - Purlilaiceu, Purlilaiceu; Saraswati, Saraswati; Ayuningtyas, Hapsari (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to determine the implementation of differentiated learning using the discovery learning model in Indonesian language subjects with the theme of local wisdom in the culinary field in each city or region in Banten Province. The research approach and method determined is qualitative description with the aim of describing and explaining the phenomena that are occurring in detail. The research results show that there are positive changes for both teachers and students when implementing differentiated learning. This can be proven by: 1) the emergence of teacher innovation and creativity in preparing learning, 2) being able to map students' abilities based on learning styles, learning readiness and learning environment by carrying out cognitive diagnostics through website-based applications. 3) obtain a thorough understanding of the material mastered by students even though the presentation of the content is different in each group. 4) increased self-confidence, motivation and collaboration have proven that students play an active role in learning so that the development of the Pancasila Learner Profile has emerged. 5) creating good cooperation between teachers and students